AC impedance measurement of zinc oxide with different heat treatment / Abbas Mahmud - Mahmud, Abbas (2011)
Zinc oxide powders were synthesized combustion method using citric acid as the precursor. The structure and morphology of synthesized powders were investigated and characterized by X-ray diffraction (XRD) and the electrochemical impedance spectroscopy (EIS). XRD results indicate that pure single phase zinc oxide of rutile structure had been obtained. It was also revealed that annealing temperature plays an important role in the formation of single phase zinc oxide powder. Conductivity studies using a.c impedance technique was used. The conductivity of the sample that annealed at 650 °C with 3 hour annealing time is the higher and follows by sample with 5 hour annealing time and sample with 24 hour annealing time.